CLIMATE IMPACT AND CULTURAL SHIFTS IN NATURAL STRUCTURES AND HUMAN LIFE: A RIVER AREAS UTILIZATION AS COMMUNITY-BASED ECOTOURISM - Isdarmanto, Isdarmanto; Dwiatmaja, Christantius; Sunarto, Hari; Abdi, Antonius Suryo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
The Climate change in world tourism can change the system of human life and its influence on nature. The development of the global digital tourism climate, selfi tourism is able to change the attitude of individual behavior in response to the demands of competitive life. The development of tourist destinations in the world, primarily from natural factors, the demands of a sharp competitive climate require tourism managers to create artificial innovations that are developed from natural potentials that are more attractive in design so that they become alternative ecotourism idols capable of boosting tourism growth that is more conducive and attractive. This research develops river ecotourism areas which are oriented to aspects of environmental development, nature preservation and local community development. This study uses qualitative research so that it can explore various aspects of the natural and humanity of the region in depth through the empirical phenomena that exist in the field. The real condition of river area which is not well managed is not in accordance with the development of Smart city, community awareness and tourism activists who are less focused. Hence, it needs community empowerment and encouraging the role of tourism activists to play more in the development of urban areas, and the use of river as ecotourism. Keywords: Ecotourism, Waterfront, Natural Resources